2011
DOI: 10.1603/en10153
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Salivary Proteins From Five Aphid (Hemiptera: Aphididae) Species

Abstract: Aphid (Hemiptera: Aphididae) saliva, when injected into host plants during feeding, causes physiological changes in hosts that facilitate aphid feeding and cause injury to plants. Comparing salivary constituents among aphid species could help identify which salivary products are universally important for general aphid feeding processes, which products are involved with specific host associations, or which products elicit visible injury to hosts. We compared the salivary proteins from five aphid species, namely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 22 publications
2
52
0
Order By: Relevance
“…This model is supported by the occurrence of low protein numbers for RWA1 and 8 (least virulent), and the highest numbers of salivary proteins for RWA2 (most virulent), with the exception of RWA5, a biotype of intermediate virulence, that displayed the lowest number of salivary proteins. Other studies have found limited genetic variation among D. noxia biotypes [37], biotypic proteome variation in whole-body extracts of S. graminum [38], and variation among salivary proteomes of separate aphid species [20] which supports the high level of variation found among RWA biotypes in our results. Our research is the first to demonstrate protein differences in the saliva of aphids at the biotype level within an aphid species.…”
Section: Variation In Protein Patterns Detected With Gel Electrophoresissupporting
confidence: 90%
See 2 more Smart Citations
“…This model is supported by the occurrence of low protein numbers for RWA1 and 8 (least virulent), and the highest numbers of salivary proteins for RWA2 (most virulent), with the exception of RWA5, a biotype of intermediate virulence, that displayed the lowest number of salivary proteins. Other studies have found limited genetic variation among D. noxia biotypes [37], biotypic proteome variation in whole-body extracts of S. graminum [38], and variation among salivary proteomes of separate aphid species [20] which supports the high level of variation found among RWA biotypes in our results. Our research is the first to demonstrate protein differences in the saliva of aphids at the biotype level within an aphid species.…”
Section: Variation In Protein Patterns Detected With Gel Electrophoresissupporting
confidence: 90%
“…There were thirty-eight individual protein bands ranging from <10 kDa to > 250 kDa and the majority of these bands were previously undetected in D. noxia [15,20]. The most intense protein bands in each RWA biotype were located at 45, 50, 80, and 95 kDa.…”
Section: Variation In Protein Banding Patterns Detected With 1-d Gel mentioning
confidence: 98%
See 1 more Smart Citation
“…One such effect is chlorosis (Heng-Moss et al, 2003;Smith et al, 2005;Botha et al, 2006;Diaz-Montano et al, 2007;Goławska et al, 2010). Highly bioactive effector molecules in aphid salivary gland secretions may cause severe damage to infested plants (Cooper et al, 2010;Cooper et al, 2011;Nicholson et al, 2012;Rao et al, 2013). Although Z. mays is one of the most important model plants and a valuable crop, there has been no published assessment of aphid-evoked changes in the total chlorophyll concentration of seedlings representing a wide range of genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, with the development of genomics and transcriptomic resources and the availability of highly sensitive proteomics technology, the composition of saliva from a number of aphid species, including the potato aphid, has been investigated (Carolan et al, 2009(Carolan et al, , 2011Chaudhary et al, 2014Chaudhary et al, , 2015Cooper et al, 2010Cooper et al, , 2011Harmel et al, 2008;Nicholson et al, 2012;Rao et al, 2013;Vandermoten et al, 2014). Almost all proteins identified in the potato aphid saliva had homologues in the pea aphid (Acyrthosiphum pisum), the only aphid with a published genome sequence (International Aphid Genomics Consortium, 2010).…”
Section: Introductionmentioning
confidence: 99%